Predicting Poor Outcome Before Endovascular Treatment in Patients With Acute Ischemic Stroke - Ramos, Lucas A.; Kappelhof, Manon; van Os, Hendrikus J. A.; Chalos, Vicky; Van Kranendonk, Katinka; Kruyt, Nyika D.; Roos, Yvo B. W. E. M.; van der Lugt, Aad; van Zwam, Wim H.; van der Schaaf, Irene C.; Zwinderman, Aeilko H.; Strijkers, Gustav J.; et al. (Frontiers in Neurology, 2020)
Abstract Background: Although endovascular treatment (EVT) has greatly improved outcomes in acute ischemic stroke, still one third of patients die or remain severely disabled after stroke. If we could select patients with poor clinical outcome despite EVT, we could prevent futile treatment, avoid treatment complications, and further improve stroke care. We aimed to determine the accuracy of poor functional outcome prediction, defined as 90-day mRS≥5, despite EVT treatment. Methods: We included 1526 patients from the MR CLEAN Registry; a prospective, observational, multicenter registry of ischemic stroke patients treated with EVT. We developed machine learning prediction models using all variables available at baseline prior to treatment. We optimized the models for high specificity both maximizing the AUC reducing the number of false positives. and positive predictive value. Results: From 1526 patients included, 480 (31%) of patients showed poor outcome. The highest area under the curve was 0.81 for random forest. The highest area under the precision recall curve was 0.69 for the SVM. The highest achieved specificity was 95% with a sensitivity of 34% for neural networks, indicating that all models contained false positives in their predictions. From 921 mRS 0-4 patients, 27 to 61 (3 to 6%) were incorrectly classified as poor outcome. From 480 poor outcome patients in the registry, 99 to 163 (21 to 34%) were correctly identified by the models. Conclusions: All prediction models showed a high area under the curve. The best-performing models correctly identified 34% of the poor outcome patients at a cost of misclassifying 4% of non-poor outcome patients. Further studies are necessary to determine whether these accuracies are reproducible before implementation in clinical practice.